Hubungan Peranan Ibu Dalam Pemeliharaan Kesehatan Gigi Mulut Terhadap Angka Kebersihan Gigi Anak Tk Bhakti Nurush Shofia Mutih Kulon Wilayah Puskesmas Wedung 2 Kabupaten Demak - Bedjo Santoso; Indiyah Sulistiyowati; Yodong Mustofa (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
ABSTRACTThe dental health problems of preschool children are dental caries and tooth-supporting tissue disease, one of which causes is an external factor that is the role of parents that is indispensable in guiding, understanding, reminding, and providing facilities to children so that children can maintain cleanliness teeth and mouth. This study aims to analyze the relationship between the role of mothers in maintaining oral health and dental hygiene rates for the children of Bhakti Nurush Shofia Mutih Kulon Kindergarten in the area of Puskesmas Wedung 2, Demak Regency. This type of research is the analytic with approach cross-sectional. The population of 108 consists of 54 mothers and 54 pre-school children. Samples were taken 30% of the total population so that 30 people were consisting of 15 mothers and 15 children. The results of the validity test of the instrument with the product-moment obtained values between 0.457 - 0.727 meaning that 20 items were valid. Instrument reliability was tested using Cronbach's alpha with a result of 0.901 which means 20 reliable question items. Results The role of parents was mostly included in the medium category at 66.7%. The plaque index of children who had both good and moderate categories was 40.0%, fewer categories were 20.0%. statistical test results Spearmen rank to show that p-value 0.001, meaning that there is a significant relationship between the role of mothers in maintaining oral health with plaque index. Children